Innovations in Public Administration: Responding to Governance Challenges in the Digital Age - Tony Pathony (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This study explores the strategic role of innovation in public administration as a response to the evolving challenges of governance in the digital age. Using a qualitative approach through library research, this paper analyzes various theoretical perspectives and empirical findings related to digital transformation in the public sector. The research highlights that innovations in public administration are not limited to the adoption of digital technologies but are also deeply embedded in institutional structures, organizational culture, and citizen engagement mechanisms. Key findings reveal that the success of public sector innovation depends on multiple interrelated factors such as transformational leadership, adaptive regulatory frameworks, technological infrastructure, and human resource capacity, particularly in digital literacy. The study also emphasizes the importance of cross-sector collaboration and localized adaptation in implementing effective digital governance. Despite significant advancements, challenges remain, including digital divides, bureaucratic inertia, and cybersecurity threats, which hinder inclusive and efficient public service delivery. Comparative insights from both developed and developing countries show that digital innovation must align with local contexts and institutional readiness to generate sustainable impact. This study contributes to the theoretical discourse by framing innovation as a multidimensional and interactive process shaped by political, technological, and societal dynamics. Practically, it offers policy recommendations to strengthen institutional capacity, foster innovation-friendly environments, and promote inclusive governance through digital means. The findings underscore the urgent need for public institutions to transition from traditional bureaucratic models to agile, citizen-centered, and data-driven governance systems that are better equipped to meet the demands of the digital era.